Cloud top temperature structural changes during the life-cycle of Saurashtra cyclone ( 1978) - NARAYANAN, M. S.; RAO, B. M. (MAUSAM, 1981)
Cloud Top Temperature (CTT) maps obtained for the first time in India from the NOAA-5 Very High Resolution Radiometer (VHRR) data recorded at Space Applications Centre. Ahmedabad have been analysed to study the intensity changes associated with the cyclonic storm of November 1978. A progressively southward movement of the deep convection cells in relation to the Central Dense Overcast (CDO) is observed from the intensifying to the final decay stage of the storms. The locations of these cells are shown to be an important factor associated with the cyclone intensity changes. The southward extension of westerlies is proposed as a possible cause of the southward shift of the deep convective cells within the CDO.